2012
DOI: 10.1186/1471-2431-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of metabolic syndrome and its components with -844 G/A and HindIII C/G PAI-1 gene polymorphisms in Mexican children

Abstract: BackgroundSeveral association studies have shown that -844 G/A and HindIII C/G PAI-1 polymorphisms are related with increase of PAI-1 levels, obesity, insulin resistance, glucose intolerance, hypertension and dyslipidemia, which are components of metabolic syndrome. The aim of this study was to analyze the allele and genotype frequencies of these polymorphisms in PAI-1 gene and its association with metabolic syndrome and its components in a sample of Mexican mestizo children.MethodsThis study included 100 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
6
1
4
Order By: Relevance
“…Our findings show that PAI-1 -675 4G/4G carriers had a higher risk of developing keloid. Several studies reported that the PAI-1 -844 A/G polymorphism may contribute to the risk of some diseases [18,19]. However, in the present study, no evidence was found of a relationship between this variant and the risk of keloid.…”
Section: Discussioncontrasting
confidence: 91%
“…Our findings show that PAI-1 -675 4G/4G carriers had a higher risk of developing keloid. Several studies reported that the PAI-1 -844 A/G polymorphism may contribute to the risk of some diseases [18,19]. However, in the present study, no evidence was found of a relationship between this variant and the risk of keloid.…”
Section: Discussioncontrasting
confidence: 91%
“…9 También en el estado de Guerrero, México, otro análisis realizado entre niños mestizos de 6 a 11 años de edad obtuvo una prevalencia de SM de 48%, incluyendo además la resistencia a la insulina. 17 En el mismo sentido, en otros países se encontraron prevalencias de SM distintas entre niños obesos: 19.6% en España 39 y 27.6% en China, 40 en comparación con el 20% registrado en México. 41 Estas variaciones podrían deberse a la situación particular de cada grupo de estudio y a los diferentes escenarios.…”
Section: Discussionunclassified
“…15 Diversas investigaciones refieren datos respecto a la prevalencia de SM en la población infantil y adolescente, desde los 6 hasta los 24 años. [16][17][18] En México se han publicado estudios cuyo propósito ha sido determinar la prevalencia de SM en escolares de 6 a 16 años, utilizando diferentes criterios como los del NCEP-ATP III, modificados para niños, y los de la IDF, con una variación de 6.7 a 44%. 9,[19][20][21] Los objetivos del presente estudio fueron estimar la prevalencia de SM y la de sus componentes, así como su asociación con la obesidad y el riesgo cardiovascular en niños en edad escolar, inscritos en escuelas públicas urbanas de siete municipios del Estado de México, México.…”
unclassified
“…A Mexican study revealed a relationship between −844 G/A and metabolic syndrome [39]. Another study revealed an association with cardio-vascular disease and dyslipidemia [40].…”
Section: Resultsmentioning
confidence: 99%